What is really involved in reading and writing - Kaplan, Robert B. (Lenguas Modernas, 2017)
The processes underlying written text encoding/decoding are more complex than has previously been assumed. More is involved than is subsumed in mechanical encoding or decoding -in penetrating the spelling, punctuation, and morphosyntax. A model is presented which considers some of the issues and teases out some factors in greater detail. It is proposed that text is not transparent even to native speakers -let alone to non-native speakers -but that the factors implicated can be isolated and addressed in classrooms to make text less opaque. At the same time, conceiving the processes as reciprocal means that understanding the factors can facilitate writing as well as reading.